Pengaruh Profitabilitas dan Solvabilitas terhadap Nilai Perusahaan pada Perusahaan Sub Sektor Kosmetik dan Keperluan Rumah Tangga yang Terdaftar di Bursa Efek Indonesia Tahun 2019-2023 - Naura Putri Assyifa; Elmira Siska (Jurnal Rimba Riset Ilmu manajemen Bisnis dan Akuntansi, 2025)
The cosmetic and household goods industry in Indonesia continues to experience growth in line with increasing consumer demand and lifestyle changes. This sector plays an important role in supporting the national economy, but it is also vulnerable to fluctuations in market dynamics, global competition, and external challenges that may affect companies’ financial performance. The performance of these companies can be assessed through financial indicators, particularly profitability and solvency, which are often linked to firm value. This study aims to analyze the effect of profitability and solvency on firm value in the cosmetic and household goods subsector listed on the Indonesia Stock Exchange (IDX) during the period 2019–2023. The research population consists of 11 companies, with 6 companies selected as the sample using purposive sampling techniques based on specific criteria. The data used are secondary data derived from financial statements obtained from the official IDX website (www.idx.co.id). The analytical method applied is quantitative with several statistical tests, including classical assumption tests, multiple linear regression, t-test, and F-test, assisted by SPSS version 22. The research findings indicate that profitability, proxied by Return on Assets (ROA), has a positive and significant partial effect on firm value (t-value 3.132 > t-table 2.04841). Solvency, proxied by the Debt to Equity Ratio (DER), also shows a positive and significant partial effect on firm value (t-value 5.810 > t-table 2.04841). Moreover, both profitability and solvency simultaneously have a positive and significant effect on firm value (F-value 86.997 > F-table 3.35). These results suggest that maintaining profitability and managing solvency effectively are key strategies for companies in enhancing firm value in a competitive market environment.